2017
DOI: 10.1002/jpln.201700293
|View full text |Cite|
|
Sign up to set email alerts
|

Interactive effects of biochar and micronutrients on faba bean growth, symbiotic performance, and soil properties

Abstract: Leguminous crops are significantly involved in the global symbiotic biological N2 Fixation (BNF), an eco‐friendly process in the agriculture system. Biochar is considered as a vital amendment in improving growth and quality of crops and soils. Few investigations have been conducted to determine the combination effect of biochar with microelements on growth of legumes and soil properties. This study was designed to study the effect of soybean straw‐derived biochar (SSDB) with or without microelements on soil mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…In contest with this study, other findings revealed that foliar spraying of zinc enhanced soybean yield, and number and weight of seeds plant −1 (Kobraee et al, 2011). Similarly, Mohamed et al (2017) stated that application of micro nutrients like zinc significantly affected 100 seed weight of faba bean. Gizawy and Mehasen (2009) also confirmed that application of zinc significantly increased 100 seed weight of faba bean compared to the control treatment.…”
Section: Seed Weightsupporting
confidence: 53%
“…In contest with this study, other findings revealed that foliar spraying of zinc enhanced soybean yield, and number and weight of seeds plant −1 (Kobraee et al, 2011). Similarly, Mohamed et al (2017) stated that application of micro nutrients like zinc significantly affected 100 seed weight of faba bean. Gizawy and Mehasen (2009) also confirmed that application of zinc significantly increased 100 seed weight of faba bean compared to the control treatment.…”
Section: Seed Weightsupporting
confidence: 53%
“…Similar results were found for cowpea, whereas the application of maize biochar significantly enhanced nodule number, shoot biomass, and grain yield, as well as nitrogen and phosphorus contents [38]. Mohamed et al [13] observed increased nodule numbers and contents of N, P, and K in plant tissue of faba bean grown in soil amended with soybean straw-derived biochar, with or without amendments of N, P and K. Yusif et al [39] found a synergistic effect of rhizobia and biochar addition on groundnut nodulation, growth and development.…”
Section: Introductionsupporting
confidence: 72%
“…An increased N concentration in plant tissue of beans was also reported by Rondon et al [59]. The combined effect of biochar and nutrients such as N, P, and K on total P and K uptake of faba bean was reported by Mohamed et al [13]. The increases in nitrogen acquisition may be related to improved soybean nodulation and N 2 fixation after biochar application [49,59].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…(Graber et al, 2010), maize (Islami et al, 2011), and wheat (Alburquerque et al, 2014) after biochar amendment. Moreover, nodule number in the cases of soybean (Mete et al, 2015) and faba bean (Mohamed et al, 2017) significantly increased due to the addition of biochar to the soil, indicating improved symbiotic performance of the plant with rhizobia. Concerning soil biochemical properties, enzyme activities were studied to rate or monitor soil fertility and productivity (Dempster et al, 2012; Song et al, 2018).…”
Section: Introductionmentioning
confidence: 99%